Reconceptualizing Islamic Epistemic Pluralism: A Critical Study of Qur’anic Hermeneutics and Contemporary Knowledge Systems - Nurhadi Nurhadi; Muhammad Tahajjudi Ghifary; Ali Banaeian Esfahani (International Forum of Researchers and Lecturers, 2024)
This study explores the integration of Islamic epistemology with modern scientific methodologies, proposing a pluralistic epistemic framework that bridges the gap between divine revelation (wahyu), rationality (aql), and empirical knowledge. The research investigates the comparative relationship between traditional Islamic knowledge systems, particularly classical Qur'anic hermeneutics, modern tafsir approaches, and contemporary scientific methods. Traditional Islamic epistemology, grounded in metaphysical and theological frameworks, often emphasizes the separation of spiritual knowledge from empirical science. However, modern scientific methodologies, which prioritize empirical observation and rational inquiry, have created challenges for reconciling Islamic thought with contemporary scientific paradigms. This study identifies common epistemic grounds, such as the use of reason, observation, and the search for truth, as shared goals between Islamic epistemology and modern science. The proposed integrative model of Islamic epistemic pluralism offers a more cohesive and relevant approach to knowledge by acknowledging both spiritual and scientific insights. This model suggests that divine revelation and empirical science can coexist in an inclusive epistemic framework, providing a more comprehensive understanding of reality. The implications of this integrative model for Islamic thought, education, and research are significant, suggesting potential for broader interdisciplinary collaboration and a more holistic approach to addressing modern challenges. The study concludes by calling for further research into practical frameworks for applying Islamic epistemic pluralism across various fields, such as social sciences, engineering, and environmental studies, to contribute to a more inclusive and dynamic global intellectual discourse.